Centerline-SMED integration for machine changeovers improvement in food industry. Issue 9 (4th July 2019) - Lozano, J.; Saenz-Díez, J.C.; Martínez, E.; Jiménez, E.; Blanco, J.
Abstract: This paper demonstrates how it is possible to combine SMED with Centerlining in complex production environments with numerous changes of format, product, raw materials and tools. This research proposes a methodology involving an initial application of Centerlining and, once the machinery and the process are stable, the subsequent implementation of SMED. Furthermore, it aims to show that it is possible to achieve improved output and reduced machinery changeover time while ensuring that the effect achieved by SMED is more stable. This increases the organizational advantages with respect to the implementation of SMED without prior application of Centerlining. The most important overall conclusion is that a successful application of SMED must always be accompanied by another type of tool or technique to maximize the results of its application. And, as presented in this work, one technique that enables significant improvements to SMED is the application of Centerlining.